The Efficacy and Safety of Once Daily versus Twice Daily Dosing of Caffeine Citrate in Apnea of prematurity: a Randomised Control Trial - Syed, Farooq; kini, Sandesh; Majeed, Abdul (Journal of Nepal Paediatric Society, 2022)
Introduction: Caffeine citrate is widely used for prevention of apnea of prematurity and helps in successful extubation from mechanical ventilation. The optimum caffeine dose in preterm infants with apnea of prematurity has been extensively investigated with varied results. The objective of our study was to compare the efficacy and safety of once versus twice daily maintenance dose of caffeine citrate in premature infants with apnea. Methods: In this study, preterm neonates with gestational age of 28 to 34 weeks, with evidence of apnea of prematurity were included. Both groups received a 20 mg / kg loading dose of caffeine citrate followed by a maintenance dose of 2.5 mg / kg every 12-hour-interval in group 1 and 5 mg / kg every 24-hour-interval in group 2, either orally or by intravenous infusion. Response to treatment, duration to achieve full feeds, possible adverse reactions were evaluated and compared among the two groups. Results: Among two groups, group 1 had early reduction in number of apneic episodes on five consecutive days after loading dose, which was statistically significant. Time taken to establish full feeds following treatment initiation was lower in group 1 compared to group 2 (median: Two vs four days) which was statistically significant. Conclusions: In this study, neonates who received twice daily maintenance dose of caffeine citrate had better outcomes in terms of early reduction in number of apneic episodes and early feed establishment when co